Pengaruh Sistem Informasi Akuntansi dan Pemahaman Akuntansi Pemerintahan terhadap Kualitas Laporan Keuangan Puskesmas di Kabupaten Demak - Saripuspita, Syafi'ah Candra; Sari, Cahyani Tunggal; Budiyono, Rokhmad (JURNAL STIE SEMARANG, 2024)
This study aims to determine the effect of Accounting Information Systems and Understanding of Government Accounting on the Quality of Financial Statements. The sampling technique in this study was using Proportional Stratified Random Sampling. The research method used is a descriptive analysis method, a statistical analysis method consisting of multiple linear regression analysis, partial significant testing (t-test) and testing the coefficient of determination (R²). The results of this study indicate that the accounting information system has no significant effect on the quality of financial reports, while the understanding of government accounting has a significant effect on the quality of the financial reports of the Community Health Centers in Demak Regency.